Analysis Of Investment Feasibility In A Water Lost Control Program: Study Case Regional Owned Enterprise - Garin Rizki Arishaldi; Nur Dhani Hendranastiti (International Journal of Islamic and Social Sciences (ISOS), 2021)
his study aims to analyze the financial feasibility of each water loss control program at PERUMDA Tirta Pakuan Bogor City as a solution in reducing the water loss. This feasibility study was conducted by calculating the NPV, Net B/C Ratio, IRR, and Payback Period for three different Scenarios, which are: (i) 100% equity, (ii) 75% equity and 25% debt, and (iii) 50% equity and 50% debt. According to the calculation, the best investment scenario being selected is the one with the highest NPV, that is Scenario 3. Not only this is supported by the value of IRR that is higher than the WACC (19.05%>17.15%), it also has the highest Net B/C Ratio. The sensitivity analysis also shows that the interest rate and proportion of loan do not have significant effects on the NPV obtained. At the same level of interest rate, the NPV obtained will be higher if the proportion of debt submitted is larger. However, for the same portion of the loan, the losses occurring will only appear if there is a change in interest rates of more than 600%.